Serum biochemical indicators in rats of different ages after replacing femoral metaphysis defects with allogeneic bone implants saturated with mesenchymal stem cells - P. M. Vorontsov; M. O. Korzh; F. S. Leontieva; V. O. Tuliakov (Zaporožskij Medicinskij Žurnal)
The aim of the study: to evaluate the course of metabolic processes after replacing femoral metaphysis defects with allogeneic bone implants saturated with allogeneic mesenchymal stem cells (MSCs) based on the analysis of serum biochemical indicators of connective tissue metabolism in laboratory rats.